2020
DOI: 10.3390/s20113279
|View full text |Cite
|
Sign up to set email alerts
|

Compressed-Domain ECG-Based Biometric User Identification Using Compressive Analysis

Abstract: Nowadays, user identification plays a more and more important role for authorized machine access and remote personal data usage. For reasons of privacy and convenience, biometrics-based user identification, such as iris, fingerprint, and face ID, has become mainstream methods in our daily lives. However, most of the biometric methods can be easily imitated or artificially cracked. New types of biometrics, such as electrocardiography (ECG), are based on physiological signals rather than traditional biological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Anyway, a systematic approach of compressed learning of ECG signal had not been done, but few have implemented compressed learning on ECG. Ching-Yao Chou et al [230] proposed a biometric user identification using ECG known as Compressed alignmentaided compressive analysis (CA-CA) algorithm, this CA-CA algorithm uses PCA based dictionary in compressed domain, where the reconstruction of ECG signal is avoided and the information is directly recovered from compressed domain resulted in a reduction of computation time by 81.08% and classified the compressed ECG signal with high accuracy. Compared to compressed learning (CL), the accuracy of the proposed algorithm was improved by 7.11%, the accuracy dropped with respect to Reconstruction learning with alignment (RL-A) and this algorithm was tested only on a small ECG database.…”
Section: Learning On Reconstructed Ecg Signalmentioning
confidence: 99%
“…Anyway, a systematic approach of compressed learning of ECG signal had not been done, but few have implemented compressed learning on ECG. Ching-Yao Chou et al [230] proposed a biometric user identification using ECG known as Compressed alignmentaided compressive analysis (CA-CA) algorithm, this CA-CA algorithm uses PCA based dictionary in compressed domain, where the reconstruction of ECG signal is avoided and the information is directly recovered from compressed domain resulted in a reduction of computation time by 81.08% and classified the compressed ECG signal with high accuracy. Compared to compressed learning (CL), the accuracy of the proposed algorithm was improved by 7.11%, the accuracy dropped with respect to Reconstruction learning with alignment (RL-A) and this algorithm was tested only on a small ECG database.…”
Section: Learning On Reconstructed Ecg Signalmentioning
confidence: 99%
“…CS combined with machine learning on ECG signal classification was simulated in the study. [ 14 15 ] The results of their study showed high accuracy in the compressed signal. The use of CS in other medical signal classifications such as EEG epileptic detection has been reported in studies.…”
Section: Introductionmentioning
confidence: 99%